A Critique of the Concept of ’Culture’ in the EFL/ESL Literature: alternative approaches to the understanding of ’Culture’ - Othman, Awras (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The ELT/EFL literature contains a good number of papers and articles reporting the attempt to apply a new methodology or a learning approach- such as the communicative approach during the 90s and learner autonomy recently- in a country different from that where it has been developed. The target country is a non-European one in most cases. Most of these reported attempts have ended either in humble results or in total failure. This is often attributed by researchers solely to the values of the national culture of the target country which are often described as opposing the principles of the new methodology, affecting all the students of this county evenly all the time and, therefore, constraining the application of the new methodology.In most of these cases the researchers end up suggesting either ’corrective training’ to help the students ’get rid of these national values’ or withdrawing completely from applying the new methodology or approach. Therefore, this paper aims at reviewing ’the standard view’ of the concept of ’culture’ in the ELT literature and at offering alternative understandings of this concept which could help researchers see factors other than the national culture affecting the application of a new methodology, and which (i.e. the factors)- if taken into consideration- would significantly help in the appropriation of a new teaching methodology or learning approach.